2018
DOI: 10.1007/978-981-10-8195-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Trichocyte Keratin Associated Proteins

Abstract: The major components of hair are keratins and keratin associated proteins (KRTAPs). KRTAPs form the interfilamentous matrix between intermediate filament bundles through extensive disulfide bond cross-linking with the numerous cysteine residues in hair keratins. A variable number of approximately100-180 genes compose the KRTAP gene family in mammals. KRTAP gene family members present a typical pattern of concerted evolution, and its evolutionary features are consistent with the evolution of mammalian hair. KRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Writing on the evolutionary sources of the KRTAPencoding genes, Wu, Irwin, and Zhang ( 8) reported that the keratin-associated proteins were con ned to the mammals, while in a later paper, Wu and Irwin wrote: "As the sequence composition of the KRTAP genes have no homology with other existing genes, it is likely that the KRTAP genes originated de novo from non-genic regions." (20). From this one might conclude that the rst KRTAP was an orphan gene, or perhaps different orphans founded the different families.…”
Section: Discussionmentioning
confidence: 91%
“…Writing on the evolutionary sources of the KRTAPencoding genes, Wu, Irwin, and Zhang ( 8) reported that the keratin-associated proteins were con ned to the mammals, while in a later paper, Wu and Irwin wrote: "As the sequence composition of the KRTAP genes have no homology with other existing genes, it is likely that the KRTAP genes originated de novo from non-genic regions." (20). From this one might conclude that the rst KRTAP was an orphan gene, or perhaps different orphans founded the different families.…”
Section: Discussionmentioning
confidence: 91%
“…The high cysteine content of EDDM is comparable to that of avian EDCRP, another cysteine-rich protein component of feathers (Strasser et al 2015), and mammalian cysteine-rich keratin-associated proteins (KRTAPs), which are components of hair and nails (Rogers et al 2001; Deb-Choudhury 2018; Plowman 2018; Wu and Irwin 2018). While KRTAPs are encoded by genes outside of the EDC, the EDCRP gene is located in the EDC but within a different region than EDDM (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, some members of the KRTAP family and HTR5A, KNG1, DRD3, HTR1D, TAS2R16, INSL5, TAS2R42, and GRM7 are considered to be the hub genes in the PPI network. Keratin-associated proteins (KRTAP) are the major components of hair [ 41 ]. KNG1 is believed to be related to the occurrence of thyroid cancer [ 42 ].…”
Section: Discussionmentioning
confidence: 99%